Reedsburg Fermentation Fest Farm/Art Dtour event: survey summary - Hadley, Shelly; Trechter, David (My University, 2012)
In October 2011, Reedsburg, Wisconsin held it's annual Fermentation Fest. A component of the event in 2011 was a 50-mile tour (Dtour) through Sauk County of art installations, artist-built roadside culture stands, rural culture education sites, and pasture performances. To evaluate the impact of this event, the Survey Research Center (SRC) at the University of Wisconsin-River Falls contacted Dtour participants (audience, artists, performers, landowners, and businesses) by email and mail in November and December 2011 and invited them to participate in a survey. Four surveys were created based on a participant's role in the Dtour. Information from the surveys are expected to provide feedback on the 2011 Dtour and guide future Dtour planning
48 p.
Keywords: Sauk County (Wis.)--Survey; Sauk County (Wis.); Agriculture--Wisconsin; Dtour